PENANGANAN SEDIMENTASI PADA PELABUHAN KUALA RAJA KABUPATEN BIREUEN - Cut Rahmawati (Center for Research and Community Service (LPPM) University of Abulyatama, 2015)
The objective of this study is to provide an alternative design of sediment problems in Kuala Raja Port that causes disadvantages for the local fishermen due to ineffective port utilization. The primary surveys conducted in this study are topographic survey, bathymetry survey, current survey and geological survey. The wind data is obtained from the Malikul Saleh Meteorological Station. Based on the tidal survey, the water surface during the tide water is 1,56 m above 0.00 m LWS. The current data shows that the flow rate is low, which is less than 1.5 m/sec whereas not interfere ships’ movement, because the standard size of ships allowed crossing the shipping lanes is planned less than 50 GT. Based on the correction using SPM nomogram acquired high waves 3.50 m with wind speed > 20 knots and the North largest fetch 490.04 miles. Sediment transport on shore of Kuala Raja beach is 46,934.59 m3/year moves from West to East. The hand bore data on the location of the planned jetty obtained SG = 2,648, Wc = 25.66, gd = 1,549, f = 31.00, c = 0.03. Therefore, the determination of the layout of jetty at Kuala Raja Port is considering the direction of sediment transport, the wave height that occurs, the field data attained and the economic feasibility. Sediment management at the Kuala Raja Port can be done within 2 (two) ways: firstly by increasing the length of the jetty on the left and the right side and, secondly by dredging the navigation channel. The length of the jetty that is needed to expand on the left side is 284 meters long and 127.65 meters long on the right side, in order to avoid the addition of sedimentation volume. The jetty’s slope is planned 1: 2 outside the channel and 1: 1 inside the navigation channel. The dredging volume at the port entrance is approximately 39,811.60 m3.